2016
DOI: 10.1021/acs.macromol.5b02158
|View full text |Cite
|
Sign up to set email alerts
|

Ionomer Self-Assembly in Dilute Solution Studied by Coarse-Grained Molecular Dynamics

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 107 publications
(241 reference statements)
7
69
0
Order By: Relevance
“…This value is very close to the chain separation of 5.6 Å in crystalline phase of Nafion with an orthorhombic unit cell ( a = 9.9 Å, b = 5.6 Å, and c = 2.8 Å) . This implies that the backbones can be aligned in parallel in the short rod‐like particles, which is in accordance with recent simulations showing association of short Nafion chains in polar solvents …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This value is very close to the chain separation of 5.6 Å in crystalline phase of Nafion with an orthorhombic unit cell ( a = 9.9 Å, b = 5.6 Å, and c = 2.8 Å) . This implies that the backbones can be aligned in parallel in the short rod‐like particles, which is in accordance with recent simulations showing association of short Nafion chains in polar solvents …”
Section: Discussionsupporting
confidence: 92%
“…23 This implies that the backbones can be aligned in parallel in the short rod-like particles, which is in accordance with recent simulations showing association of short Nafion chains in polar solvents. 24,25 The outer surface area of this cylinder is 107 nm 2 and the specific surface, that is, the area per one charge is 0.89 nm 2 . This value is close to the estimated values of the rod-like particles in most of the polar solvents but larger than the value of about 0.6 nm 2 in H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Significant attention has been focused on understanding how perfluorosulfonic ionomer (PFSI) interacts in different solvent systems because of its complex structure. 13,14 PFSA is characterized by a hydrophobic backbone and a hydrophilic side chain and does not form a true solution but instead has the tendency to form a colloid structure when dispersed in a solvent. Uchida et al demonstrated that PFSA properties were fundamentally a function of the solvents dielectric constant.…”
mentioning
confidence: 99%
“…Their size and shape depends on the solvent and the equivalent weight of the ionomer. Ghelichi and Eikerling reported from a general modelling approach including a variety of different ionomer architectures that the particle size depends on the detailed molecular structure and the properties of the solvent (24). The bundles have a dense hexagonal packing consisting of ionomer backbones, the sulfonic acid groups are oriented to the sides.…”
Section: Dispersion Particlesmentioning
confidence: 99%